Modulatory actions of des-aspartate angiotensin 1 on vascular reactivity and endothelial function in aorta from spontaneously hypertensive rats / Loh Wei Mee - Loh, Wei Mee (2016)
Hypertension or chronic elevation of arterial blood pressure is associated with endothelial dysfunction. Imbalance of vasodilators and vasoconstrictors released from the endothelium contributes to the development of endothelial dysfunction in hypertension. Renin angiotensin system (RAS) is one of the major physiological systems contributing to the regulation of arterial blood pressure and angiotensin II (Ang II) is the most active component in RAS. Ang II exerts various physiological functions through its interaction with angiotensin type 1 and type 2 receptors (AT1R and AT2R, respectively). Stimulation of AT1R activates signaling cascades that causes vasoconstriction, oxidative stress, vascular remodeling and endothelial dysfunction contributing to the pathophysiology of hypertension. In contrast, Ang II causes vasodilatation, inhibits proliferation and induces apoptosis through activation of AT2R. Des-aspartate angiotensin I (DAA-I), a nonapeptide of the RAS is known to counteract the various pathological effects attributed to Ang II. The nonapeptide showed antihyperplastic, anti-cardiac hypertrophy, anti-hyperglycemic, anti-inflammatory and antiviral properties in in vivo and in vitro studies. Although earlier studies have demonstrated various beneficial effects, little is known on the modulatory effect of DAA-I on vascular and endothelial function in hypertensive rats. Thus, the objectives of this present study are 1) to determine the modulatory effect of DAA-I on vascular responses to endothelial –dependent vasoconstrictor (angiotensin II) and to endothelial – dependent [acetylcholine (ACh)] and –independent [sodium nitroprusside (SNP)] relaxation in isolated aorta from Wistar Kyoto rats (WKY) and Spontaneously Hypertensive rats (SHR), 2) to determine the effect of DAA-I on angiotensin II-induced oxidative stress in the vascular tissues from hypertensive rats; and 3) to investigate the molecular mechanisms underlying the protective effects of DAA-I. iv Isometric tension experiments were carried out to study the vasomodulatory effects of DAA-I on vascular responses in SHR aorta. Several pharmacological inhibitors were tested to determine the mechanisms of modulatory action of DAA-I. Total nitrate and nitrite levels were assessed using a colorimetric method and reactive oxygen species (ROS) were measured by dihydroethidium (DHE) fluorescence and lucigenin-enhanced chemiluminescence in order to investigate the effect of DAA-I on oxidative stress. The present study demonstrated that DAA-I has no effect on WKY aorta but it significantly attenuated Ang II-induced contraction in the isolated aortic rings from SHR. The attenuation of DAA-I on Ang II contraction was blunted in the rings without endothelium and in the presence of L-NAME (nitric oxide synthase inhibitor) and ODQ (soluble guanylate cyclase inhibitor), indicating the action of DAA-I is dependent of nitric oxide/ sGC pathway. The effect of DAA-I on Ang II-induced contraction was significantly reduced by losartan (AT1 receptor antagonist) and partially reversed by PD123319 (AT2 receptor antagonist), indicating both angiotensin receptors modulate the actions of DAA-I. In the presence of Ang II, total nitrate and nitrite levels were increased in DAA-I, losartan and tempol treated-SHR tissues while ROS level was reduced by DAA-I and the latter inhibitors. Treatment with DAA-I significantly enhanced ACh-induced relaxation in SHR aortas but not in WKY whilst SNP-induced relaxation remained unaltered in the WKY and SHR. Losartan and L-NAME reduced the DAA-I potentiated ACh–induced relaxations in the SHR aorta. Furthermore, the sensitivity to ACh in DAA-I -treated tissues was reduced in the presence of PD 123319. In summary, the present study demonstrated that DAA-I exerts vasoprotective effect on th vascular and endothelium function in the aorta from SHR but not in WKY. The nonapeptide improves the endothelial function by attenuating Ang II-induced contraction and potentiating ACh-induced relaxation. Data obtained shows that the actions of DAA-I is endothelium-dependent. The protective effect of DAA-I is due to v the increase of NO bioavailability and reduced ROS by interfering with Ang IImediated, NADPH oxidase derived oxidative stress. In conclusion, DAA-I improves endothelial function in SHR by counteracting AT1R –mediated effects.